2020
DOI: 10.1111/coa.13624
|View full text |Cite
|
Sign up to set email alerts
|

Preradiation tooth extraction and jaw osteoradionecrosis: Nationwide population‐based retrospective study in Taiwan

Abstract: Head and neck cancer (HNC), representing 3% of all cancers, has been ranked as the sixth to eighth most common cancer type, with increasing global prevalence. 1 Despite advances in treatment, the mortality and morbidity rates remain high. 2 More than 70% of patients with HNC require radiotherapy (RT). 3,4 Oral complications (both acute and chronic effects) are common in patients receiving RT involving the oral cavity, including mucositis, infection, saliva change, fibrosis, sensory dysfunction, dental caries, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 46 publications
(117 reference statements)
1
7
0
4
Order By: Relevance
“…These findings are consistent with the study performed by Huang et al 24 that demonstrated an increased incidence of ORN in patients with pre-RT extractions performed within 2 weeks vs patients who did not undergo extractions. In a nationwide population-based retrospective study by Liao et al, 25 the incidence of ORN among 5062 patients with head and neck cancer with at least 1 tooth extraction pre-RT was 1.03%, results that are in keeping with our findings. However, the authors reported that pre-RT extractions performed 1 to 7 days before RT did not increase the risk of ORN compared with pre-RT extractions performed 7 to 21 days before RT.…”
Section: Discussionsupporting
confidence: 92%
“…These findings are consistent with the study performed by Huang et al 24 that demonstrated an increased incidence of ORN in patients with pre-RT extractions performed within 2 weeks vs patients who did not undergo extractions. In a nationwide population-based retrospective study by Liao et al, 25 the incidence of ORN among 5062 patients with head and neck cancer with at least 1 tooth extraction pre-RT was 1.03%, results that are in keeping with our findings. However, the authors reported that pre-RT extractions performed 1 to 7 days before RT did not increase the risk of ORN compared with pre-RT extractions performed 7 to 21 days before RT.…”
Section: Discussionsupporting
confidence: 92%
“…Células epiteliais, endoteliais e hematopoiéticas são afetadas logo após o início da terapia. As glândulas salivares e células ósseas são mais resistentes à radiação, porém, com a degradação vascular endotelial da cavidade oral, acabam sofrendo um comprometimento ao longo do tempo 6 . Sabe-se que o trauma é a maior causa de osteonecrose, secundariamente, ocorre por motivos vasculares, capacidade osteoclástica de reabsorção óssea comprometida ou morte celular óssea 10 .…”
Section: Mecanismo Radioterápicounclassified
“…A melhor maneira de tentar diminuir os riscos de uma complicação pós-cirúrgica em pacientes oncológicos é realizar a exodontia de dentes comprometidos periodonticamente ou com coroas afetadas de forma irreversível antes do início da terapia radioativa. Porém, o risco de exacerbação da ORN é aumentado bastante quando são feitas exodontias antes, durante ou após o tratamento radioterápico 6,7,21 .…”
Section: Osteorradionecroseunclassified
See 2 more Smart Citations